Nephron-sparing surgery for treatment of reninoma: a rare renin secreting tumor causing secondary hypertension - Torricelli, Fabio Cesar Miranda; Marchini, Giovanni Scala; Colombo, José Roberto; Coelho, Rafael Ferreira [UNESP]; Nahas, Willian Carlos [UNESP]; Srougi, Miguel [UNESP] (International Braz J Urol : Official Journal Of The Brazilian Society Of Urology, 2015)
A 25-year-old hypertensive female patient was referred to our institution. Initial workup exams demonstrated a 2.8 cm cortical lower pole tumor in the right kidney. She underwent laparoscopic partial nephrectomy without complications. Histopathologic examination revealed a rare juxtaglomerular cell tumor known as reninoma. After surgery, she recovered uneventfully and all medications were withdrawn. Case hypothesis: Secondary arterial hypertension is a matter of great interest to urologists and nephrologists. Renovascular hypertension, primary hyperadosteronism and pheocromocytoma are potential diagnosis that must not be forgotten and should be excluded. Although rare, chronic pyelonephritis and renal tumors as rennin-producing tumors, nephroblastoma, hypernephroma, and renal cell carcinoma might also induce hypertension and should be in the diagnostic list of clinicians. Promising future implications: Approximately 5% of patients with high blood pressure have specific causes and medical investigation may usually identify such patients. Furthermore, these patients can be successfully treated and cured, most times by minimally invasive techniques. This interesting case might expand knowledge of physicians and aid better diagnostic care in future medical practice.